Association between ophthalmoscopic changes and obstetric outcomes in pre-eclampsia and eclampsia - Dasgupta, Sujoy; Ray, Payal Banerjee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorder is a major cause of maternal and perinatal mortality and morbidity. The widespread endothelial dysfunction associated with preeclampsia can affect the choroid and the retina leading to characteristic ophthalmoscopic changes. So, we tried to find out the association between ophthalmoscopic changes and obstetric outcomes in women with preeclampsia-eclampsia. Methods: In a comparative, prospective study carried out from July 2011 to July 2015 in Medical College, Kolkata and KPC Medical College, Kolkata we included antenatal women with pre-eclampsia and eclampsia. Based on the ophthalmoscopic findings they were divided into two groups; group A (no ophthalmoscopic abnormalities) and group B (having ophthalmoscopic abnormalities). The results were analyzed by standard statistical methods. Results: Out of the total 200 women included, 102 women belonged to group A and 98 to group B. Majority of the patients were ophthalmologicaly asymptomatic. Most common fundoscopic abnormality in group B was focal arteriolar narrowing. Women in group B had significantly higher level of blood pressure, proteinuria and thrombocytopenia. The need of multiple drugs, incidence of HELLP syndrome and oliguria, rate of Caesarean section and CCU admission were significantly higher in group B compared to group A. There was significantly higher incidence of perinatal complications in group B, viz: IUGR, low birth weight, low Apgar score and NICU admission. Conclusions: Ophthalmoscopic changes correlate positively with adverse feto-maternal outcomes in preeclampsia. Fundoscopy should be carried out in all preeclamptic mother irrespective of the visual symptoms.